“Beyond the Kitchen Door”: Racialised Female Domestic Labourer’s Mobility Experiences in Anna Muylaert’s The Second Mother - Francianne dos Santos Velho (Alphaville: Journal of Film and Screen Media, 2024)
The successful Brazilian fictional film The Second Mother (Que horas ela volta?, 2015), directed by Anna Muylaert, illustrates that mobility is chiefly limited or stagnant for the main character, Val (Regina Case), a live-in racialised female domestic labourer who migrates from the Brazilian northeast to the southeast to work in the house of a wealthy family in São Paulo. However, the film subtly shapes Val’s mobility as a more active, unrestrained experience once her daughter arrives in town ten years later. My goal is to understand the fundamental factors influencing Val’s range of motions. Building upon on the cultural geography notion of mobility as a socially produced movement of time and space, I look at how control over Val’s ability to move derives from the embodiment of practices of power built on derogatory discourses around the ideas of the doméstica (“maid”) and the domestic spatial and interpersonal emotional relations ingrained in class, gender, and the racial dimensions of Brazil’s former colonial, plantation-based patriarchal society. On the other hand, Val begins to disembody the powerful practices that previously controlled her mobility. I argue that the spatial, social, emotional, and bodily mobility gained by Val, echoing the Brazilian period of empowerment for the working classes, reflects gains from law such as PEC das Domésticas EC 72/2013 and Lei Complementar 150/2015.